Implementation of EMR System in Indonesian Health Facilities: Benefits and Constraints – A Case Study of Two Clinics in Central Java - Juliansyah, Rasyid; Aqid, Bukhori; Salsabila, Andien Putri; Nurfiyanti, Kurnia (UI Scholars Hub, 2025)
This paper delves into the widespread implementation of Electronic Medical Records (EMR) within healthcare facilities across Indonesia. It addresses the challenges encountered by clinic owners and healthcare providers in transitioning to these digital systems. The study is supported by empirical data collected through a mixed-method approach, combining internal data from Klinik Pintar with qualitative validation from key stakeholders responsible for clinic operations. The research focuses on two case studies: Lembaga Pemasyarakatan (LAPAS) II Purwokerto Clinic and Palang Merah Indonesia (PMI) Purbalingga Clinic, where the adoption of EMR is analyzed in terms of efficiency, compliance with regulatory standards set by the Ministry of Communication and Informatics (Kementerian Komunikasi dan Informatikal – Kominfo) and the Ministry of Health (Kementerian Kesehatan – Kemenkes), and its impact on daily healthcare workflows. Through in-depth interviews and observational studies, the perspectives of clinic administrators, healthcare professionals, and information technology (IT) personnel are explored to understand the benefits and constraints of EMR implementation in real-world settings. The findings highlight key factors influencing successful EMR adoption, including user training, infrastructure readiness, and regulatory compliance. Additionally, barriers such as resistance to change, technical limitations, and integration challenges with existing healthcare systems are discussed. This study provides valuable insights for policymakers, healthcare providers, and technology developers in enhancing the effectiveness of EMR implementation in Indonesian healthcare facilities.